2014
DOI: 10.1007/s00441-014-1997-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of visfatin on the regulation of inflammation and apoptosis in the spleen of LPS-treated rats

Abstract: The purpose of the present study is to determine if visfatin is involved in inflammation or apoptosis induced by LPS in rat. Forty Wistar rats were divided into four groups: saline group, LPS group, visfatin group and Visfatin + LPS co-stimulated group. Spleen samples from each group of rats were collected for study. The spleen structure was examined by histological imaging. Apoptosis was evaluated with TUNEL reaction. Caspase-3 was detected with immunohistochemistry and western blot. The apoptosis-related gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 74 publications
2
26
0
1
Order By: Relevance
“…Yamano et al 19 noted an increased percentage of splenic red pulp and macrophages in mice fed a HFD, and elemental iron was deposited mainly in red pulp. During splenomegaly, many immune cells are released to participate in immune defense when the host is infected 11,20 . In the present study, the spleen structures showed differences among different treatment groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamano et al 19 noted an increased percentage of splenic red pulp and macrophages in mice fed a HFD, and elemental iron was deposited mainly in red pulp. During splenomegaly, many immune cells are released to participate in immune defense when the host is infected 11,20 . In the present study, the spleen structures showed differences among different treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with intracellular pathogens also induces the apoptosis of host cells by regulation of Bcl-2 and Bax 39 . Xiao et al 11 found that increased SC apoptosis in LPS-treated rats could be promoted by down-regulation of Bcl-2 expression and up-regulation of Bax expression. Interestingly, in the present study, expressions of gene and protein of the Bcl-2 and Bcl-2: Bax ratios in SCs in DIO-group mice increased, whereas expressions of the Bax gene and protein decreased, after E. coli infection.…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin stimulates TNF, IL-6, and IL-1β secretion in monocytes and is also involved in macrophage differentiation and the release of cytokines in a c-Jun N-terminal kinase-and nuclear factor κB-dependent manner [18,19]. In addition, in rats visfatin participates in inflammatory processes in the spleen by modulating both anti-inflammatory and proinflammatory cytokines, such as IL-4, IL-6, TNF, and IL-10, and contributes to apoptosis in the spleen via the mitochondrial pathway [16]. In a study involving rats, the myocardial expression of visfatin increased after the injection of LPS, and the co-administration of a visfatin inhibitor reduced myocardial inflammation and damage and improved cardiac function [14].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that visfatin promotes lung damage and myocardial impairment under acute inflammatory conditions and that the inhibition of visfatin attenuates these disorders [14,15]. In addition, it has been shown that visfatin participates in inflammatory responses in the spleen [16]. However, few studies have comprehensively evaluated the in vivo response of visfatin to septic stress.…”
Section: Introductionmentioning
confidence: 98%
“…The regional localization of sox5 and Sox6 was examined by IHC method with little modification [30] . The expression of Sox5 and Sox6 were checked in the testes of two-week-old and adult (42 days) male mouse and three mice were used in each age group.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%